Humor During Pandemic in Romania on Facebook - Claudiu Stefani (Culture e Studi del Sociale)
During the pandemic, finding coping mechanisms for anxiety, stress and isolation will be critical. Humor has always been a way to overcome anxiety and insecurity and is present in all dramatic situations in Romania.The purpose of this study is to analyze the content of humorous messages, the topics addressed, their characteristics and their dissemination.The method used was the content analysis of the messages broadcast on the social network Facebook during March - April 2020 in Romania.The results obtained show us that the main forms of diffusion of humorous messages is the Power point umor, photos, written message followed by video material with one or more protagonists in domestic contextsand poetry. The main topics covered are: the threat, the protective measures, quarantine, the efficiency of the health system, the changes in the lifestyle and their implications. The main way to spread is to roll messages on networks from the initiators of conversations. The main purpose of the messages is to neutralize the threat in the collective imaginary and to regain the symbolic control.